The Effectiveness of the Itik Land Pop Up Store Advertising Message to Instagram Followers @myyellowduckling - Ajeng Lintang Saraswati; Ido Prijana Hadi; Astri Yogatama (Journal of Content and Engagement, 2024)
My Yellow Duckling is a local brand that sells duck-themed merchandise. This brand started its business in 2019 and comes from the city of Surabaya. Starting with a drawing hobby from the owner of My Yellow Duckling, it led her to start transforming her draw into a product with selling value. She sells duck-themed merchandise, such as dolls, sticker, keychain, enamel pin, pouch, headband, and so on. My Yellow Duckling sells their product online via Shopee marketplace and offline by open a pop-up store in collaboration with the event market in Surabaya. In January 2024, My Yellow Duckling for the first time opened a pop-up store independently in Malang under the name Itik Land. To advertise their event, they use Instagram for share the message to consumer. This study uses SOR theory to determine the effectiveness of advertising messages to the audience. Advertising messages delivered will be measured effectively using AISAS models with 5 indicator, Attention, Interest, Search, Action, and Share. This type of research is descriptive with a quantitative approach. The study took data using an online questionnaire against 100 respondents using non-probability sampling techniques. The results of this study showed that messages of pop-up ads on Instagram followers @myyellowduckling proved effective with the highest average score at the attention level.